The PharmWatch programme: challenges to engaging the community pharmacists in Jamaica - Gossell-Williams M; Adebayo SA (Centro de Investigaciones y Publicaciones Farmaceuticas, 2008)
In February 2006, there was a renewed effort to encourage reporting of adverse drug reactions (ADRs) in Jamaica. It involved renaming the process the "PharmWatch" programme and revising the reporting form.Objectives: The aims of this study were to assess the attitudes of community pharmacists to ADR reporting and to assess their utilization of the PharmWatch programme. Methods: The survey was conducted in January 2007, involving 102 community pharmacists islandwide. A questionnaire was designed to assess their attitudes towards ADR reporting, their awareness of the PharmWatch programme and also to collate number of ADRs through recall. Pharmacists were then followed prospectively to collect ADRs occurring over the next three months using the PharmWatch form. Results: Although most of the pharmacists involved in the survey had more than five years of experience, the majority (67%) were not aware of the PharmWatch programme; however, 86% of the responding pharmacists indicated that they accepted that ADR reporting was a professional responsibility. They identified "reaction already known", "more information needed about reporting ADRs" and "lack of time" as key factors that would cause non-reporting. One hundred and twenty eight retrospective ADRs were collected; none were reported to the Ministry of Health directly, while two were reported to the respective drug companies. A three month prospective follow-up with pharmacists yielded 45 reports. The most common ADR reports among both the retrospective and prospective data were associated with anti-infectives. Conclusions: The results suggest that awareness of the PharmWatch programme is not adequate to facilitate active participation in ADR reporting. More proactive interventions, such as continuous training and encouragement in the use of ADR reporting should be considered.